1991
DOI: 10.1017/s0021859600076103
|View full text |Cite
|
Sign up to set email alerts
|

Boron tolerance in wheat in relation to soil salinity

Abstract: A screenhouse study in Haryana in 1986/87 evaluated the effect of boron on the wheat cultivar WH147 grown in pots in a sandy soil at three salinities. Before sowing, 0-9 mg B/kg soil was added. Without added B the crop produced significantly more grain at electrical conductivity of the saturation extract (EC e ) 6 dS/m than at other salinities, but at EC e 8 dS/m yields were similar to those in nonsaline (EC e 0-8) soil. Grain yield in nonsaline soil was not affected significantly even at the highest concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
2
5
1
Order By: Relevance
“…Toxicity symptoms were less visible on plants inoculated with mycorrhiza compared with non-inoculated plants. Contrary to our results, Manchanda & Sharma (1991) reported that increasing B toxicity symptoms in wheat occurred in all treatments having similar or low total shoot B concentrations. There is currently no available explanation for these contrary findings.…”
Section: Relative Yieldcontrasting
confidence: 99%
“…Toxicity symptoms were less visible on plants inoculated with mycorrhiza compared with non-inoculated plants. Contrary to our results, Manchanda & Sharma (1991) reported that increasing B toxicity symptoms in wheat occurred in all treatments having similar or low total shoot B concentrations. There is currently no available explanation for these contrary findings.…”
Section: Relative Yieldcontrasting
confidence: 99%
“…Although moderate and high levels of salinity did not significantly affect B content in aerial part, root, or whole seedling, a finding also reported by Manchanda and Sharma (1991), the lowest dose of NaCl significantly increased B to a degree similar to that seen for N, P, K, Fe, and Mn.…”
Section: Resultssupporting
confidence: 81%
“…The boron toxicity symptoms had been recently observed in chickpea [1], wheat [2,3], eucalyptus [4] and in stems of Prunus rootstocks [5]. The mechanism of B toxicity is still a matter of speculation.…”
Section: Introductionmentioning
confidence: 99%